Book review: "Psychology in context" - Foster, Don (PINS-Psychology in Society, 2025)
K. F. Mauer and A. I. Retief (eds.) (1987) Psychology in context: Cross-cultural research trends in South Africa. HSRC Investigation into Research Methodology; research report series 4. Pretoria: Human Sciences Research Council. 225pp. + xii. R20 + GST. The seven papers presented here emerged from a one-day HSRC seminar in July 1985 with a focus on current trends in cross-cultural research psychology. The participants were apparently invited due to their established interest and active involvement in the field, their divergence in approach and their concern for methodological issues. The result is an interesting, wide-ranging and challenging set of papers - a worthy contribution to the conteaporary debate about psychology in South Africa.